A Nod to disease vectors: mitigation of pathogen sensing by arthropod saliva - Sakhon, Olivia; Severo, Maiara; Kotsyfakis, Michail; Pedra, Joao (Frontiers in Microbiology, 2013)
Arthropod saliva possesses anti-hemostatic, anesthetic, and anti-inflammatory properties that facilitate feeding and, inadvertently, dissemination of pathogens. Vector-borne diseases caused by these pathogens affect millions of people each year. Many studies address the impact of arthropod salivary proteins on various immunological components. However, whether and how arthropod saliva counters Nod-like (NLR) sensing remains elusive. NLRs are innate immune pattern recognition molecules involved in detecting microbial molecules and danger signals. Nod1/2 signaling results in activation of the nuclear factor (NF)-kB and the mitogen-activated protein kinase (MAPK) pathways. Caspase-1 NLRs regulate the inflammasome – a protein scaffold that governs the maturation of interleukin (IL)-1β and IL-18. Recently, several vector-borne pathogens have been shown to induce NLR activation in immune cells. Here, we provide a brief overview of NLR signaling and discuss clinically relevant vector-borne pathogens recognized by NLR pathways. We also elaborate on possible anti-inflammatory effects of arthropod saliva on NLR signaling and microbial pathogenesis for the purpose of exchanging research perspectives.